Consumption Based Estimates of Urban Chinese Growth - Chamon, Marcos; de Carvalho Filho, Irineu (Washington, D.C. : International Monetary Fund, 2013)
This paper estimates the household income growth rates implied by food demand in a sample of urban Chinese households in 1993-2005. Our estimates, based on Engel curves for food consumption, indicate an average per capita income growth of 6.8 percent per year in 1993-2005. This figure is slightly larger than the 5.9 percent per year obtained by deflating nominal incomes by the CPI. We attribute this discrepancy to a small bias in the CPI, which is of a similar magnitude to the one often associated with the CPI in the United States. Our estimates indicate stronger gains among poorer households, suggesting that urban inflation up to 2005 in China was 'pro-poor,' in the sense that the increase in the cost of living for poorer households was smaller than for the average one.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet